Acknowledgement to Reviewers of Pharmaceuticals in 2017 - Pharmaceuticals Editorial Office (Pharmaceuticals, 2018)
Peer review is an essential part in the publication process, ensuring that Pharmaceuticals maintains high quality standards for its published papers[...]